Improving students' creative thinking in biology learning through Remap-TPS integrated flipped classroom - Ramdhani , Suci Arsi; Zubaidah , Siti; Prabaningtyas , Sitoresmi (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2024)
Implementing the Remap-TPS integrated flipped classroom has not yet been carried out to improve creative thinking skills in biology learning. This study aims to determine the effect of the Remap-TPS integrated flipped classroom model on students' creative thinking skills in biology learning. This study is a mixed method. The research design used was a pretest-posttest nonequivalent control group design. The research sample comprised 72 class X students at SMAN 9 Malang, East Java, Indonesia. They were divided into one experimental class and one control class. The Remap-TPS integrated flipped classroom was taught in the experimental class, while the TPS model was taught in the control class. Quantitative data was collected through pretest and posttest using essay question that refer to creative thinking indicators: curiosity, fluency, originality, elaboration, flexibility, divergent, messiness/risk taking and with others. This essay's questions have previously been tested to show valid and reliable results because Cronbach's alpha value is 0.778. Qualitative data is used together with quantitative data from the results of student answers. Analysis was carried out using the ANCOVA test with a significance level of 5%, then continued with the LSD test. Data is also explained qualitatively from the results of student answers. The study results show that the Remap-TPS integrated flipped classroom model affects students' creative thinking skills. This is proven by a significance value of 0.00<0.05. Therefore, the Remap-TPS integrated flipped classroom can be used as an alternative learning model to improve students' creative thinking in biology learning. Implementing the Remap-TPS integrated flipped classroom requires adapting learning instruments and tools to the learning model used and the skills measured to improve learning activities, especially in improving students' creative thinking skills.